2017
DOI: 10.23986/afsci.60293
|View full text |Cite
|
Sign up to set email alerts
|

Effects of HPS and LED lighting on cucumber leaf photosynthesis, light quality penetration and temperature in the canopy, plant morphology and yield

Abstract: In Nordic countries during the winter months supplemental lighting is essential for year-round cucumber production. In this research the effects of full HPS (top and interlights) illumination is compared to hybrid (HPS top, LED interlights) and full LED (top and interlights). The results showed that fruit yield was highest in the HPS-LED treatment whereas the electrical use efficiency (kg yield J -1 ) increased when HPS was replaced with LED. In LED-LED the light use efficiency (g fruit FW mol -1 PAR) was high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 17 publications
2
22
0
1
Order By: Relevance
“…In this article, we provide evidence that LED lighting with an emission spectrum that partially matches the range of 400 to 700 nm can accelerate plant growth and increase the yield of tomatoes. Similar results in terms of the stem development were demonstrated for cucumbers, sweet basil, and tomatoes when a combination of blue, green, and red LEDs (Särkkä et al, 2017); blue, yellow, and red LEDs (Carvalho et al, 2016); or only green LEDs combined with daylight (Snowden et al, 2016) was used, respectively. Our yield data, however, are different to others, who have reported that a LED lighting with an emission spectrum that is optimized for chlorophyll absorption (blue and red) produces similar or even less yield than HPS lighting (Dueck et al, 2011;Gomez et al, 2013;Fanwoua et al, 2019).…”
Section: Plant Growth and Yield Under Different Supplementary Lightingssupporting
confidence: 73%
“…In this article, we provide evidence that LED lighting with an emission spectrum that partially matches the range of 400 to 700 nm can accelerate plant growth and increase the yield of tomatoes. Similar results in terms of the stem development were demonstrated for cucumbers, sweet basil, and tomatoes when a combination of blue, green, and red LEDs (Särkkä et al, 2017); blue, yellow, and red LEDs (Carvalho et al, 2016); or only green LEDs combined with daylight (Snowden et al, 2016) was used, respectively. Our yield data, however, are different to others, who have reported that a LED lighting with an emission spectrum that is optimized for chlorophyll absorption (blue and red) produces similar or even less yield than HPS lighting (Dueck et al, 2011;Gomez et al, 2013;Fanwoua et al, 2019).…”
Section: Plant Growth and Yield Under Different Supplementary Lightingssupporting
confidence: 73%
“…Another study ( Wallace and Both, 2016 ), compared PPNE in LED lamps from different manufacturers, presenting values of 1.4 μmol J −1 (Valoya R150 NS1, RB = 2, PPFD = 184 μmol m −2 s −1 ), 0.8 μmol J −1 (Orbitec LED tower, RB = 3, PPFD = 84 μmol m −2 s −1 ) and 1.4 μmol J −1 (Cree 18W Daylight, RB = 1.3, PPFD = 4 μmol m −2 s −1 ). PPNE was also shown to be around 1.3 μmol J −1 in a red-blue top-light (Valoya AP-67, RB = 3, PPFD = 160 μmol m −2 s −1 ) ( Särkkä et al, 2017 ). Nájera et al (2018) reported PPNE to range 0.9 (Valoya AP-67, RB = 3, PPFD = 64 μmol m −2 s −1 ) to 1.2 (Valoya AP673, RB = 5, PPFD = 85 μmol m −2 s −1 ), although details in the measurements performed for quantifying electricity consumption or R:B ratio were lacking.…”
Section: Discussionmentioning
confidence: 99%
“…This differs from the existing supplementary lighting system of the Venlo-type greenhouses that mainly aims to increase light intensity. Moreover, the greenhouse temperature was increased by ~1-1.4°C during the experiment due to the application of HPS lamps that emit near infrared radiation, which also positively affects plant growth and development (Särkkä et al, 2017).…”
Section: Discussionmentioning
confidence: 99%